Analysis of Maqashid Syariah on Marriage Annulment Due to Psychological Coercion (Critical Study of the Ratio Decidendi of the Jantho Sharia Court Decision Number 226/Pdt.G/2024/MS.Jth) - Di Muhammad Faiz; Misran Misran; Azmil Umur (MAQASIDI: Jurnal Syariah dan Hukum published by the Islamic Criminal Law Program of the Sharia and Islamic Economics Department at the Sekolah Tinggi Agama Islam Negeri Teungku Dirundeng Meulaboh, 2026)
Marriage in Islamic law and positive law in Indonesia is based on the principle of willingness (ridha) of the bride-to-be. Conflict arises when the contract is carried out under psychological pressure or coercion (ikrah), thus undermining the fundamental purpose of the sharia. This study presents a critical analysis of the Jantho Syar'iyyah Court Decision Number 226/Pdt.G/2024/MS.Jth, which granted the application for annulment of marriage caused by threats and psychological pressure against the Plaintiff. This study aims to examine the juridical and philosophical justification of the decision through the lens of Maqashid Syariah (sharia goals), especially in the aspects of life protection (Hifz al-Nafs) and damage prevention (Dar'ul Mafasid). The normative juridical research method with a case study approach is used to analyze legal norms (article 27 KHI, p.45)